Some impediments to child sexual abuse interventions and corresponding social work implications: reflections on the Zimbabwean Victim Friendly System - Muridzo, Noel G.; Chikadzi, Victor (Springer Science and Business Media B.V., 2021)
Child sexual abuse is a multifaceted children’s rights issue and a global problem of considerable extent. It has adverse effects for child survivors and their ecological environments. Using qualitative data from a multiple-case study research project, the current paper discusses some of the impediments hindering effective service provision within the institutional arrangements that respond to child sexual abuse cases in Zimbabwe. The Victim Friendly System is a confluence of multisectoral and multistakeholder professionals from different governmental and nongovernmental organizations that offer integrated and coordinated services targeting primary, secondary and tertiary levels of child sexual abuse prevention and mitigation. While the Victim Friendly System has made significant strides in providing better service delivery outcomes to direct and indirect victims of child sexual abuse, there remains some service provision gaps that hinder its effectiveness. These impediments include limited coverage of services due to an urban bias, services remaining largely unknown to the public owing to poor visibility, and the cost burden associated with accessing services. The authors argue that these gaps constrain children’s access to much needed intervention. This constitutes rights violations for CSA survivors. The paper ends by discussing corresponding implications for social work practice.